Neurological manifestations of calcific aortic stenosis - I. V. Egorov (Неврология, нейропсихиатрия, психосоматика, 2014)
Despite being thoroughly studied, senile aortic stenosis (AS) remains a disease that is frequently underestimated by Russian clinicians. Meanwhile, its manifestations can not only deteriorate quality of life in patients, but can also be poor prognostic signs. The most common sequels of this disease include heart failure and severe arrhythmias. However, there may be also rare, but no less dangerous complications: enteric bleeding associated with common dysembriogenetic backgrounds, infarctions of various organs, the basis for which is spontaneous calcium embolism, and consciousness loss episodes. The latter are manifestations of cardiocerebral syndrome. Apart from syncope, embolic stroke may develop within this syndrome. There is evidence that after syncope occurs, life expectancy averages 3 years. Global practice is elaborating approaches to the intracardiac calcification prevention based on the rapid development of new pathogenetic ideas on this disease. In particular, it is clear that valvular calcification is extraskeletal leaflet ossification rather than commonplace impregnation with calcium salts, i.e. the case in point is the reverse of osteoporosis. This is the basis for a new concept of drug prevention of both calcification and the latter-induced heart disease. But the view of senile AS remains more than conservative in Russia. The paper describes a clinical case of a rare complication as cerebral calcium embolism and discusses the nature of neurological symptoms of the disease, such as vertigo and syncope.